Physiology and transcriptomic reveals the toxic effect of acute acetamiprid exposure on noble scallop Chlamys nobilis - Yetao Zeng; Dewei Cheng; Beiyu Yan; Qingyao Lu; Qing Lin; Weili Wang; Hongkuan Zhang; Huaiping Zheng (Marine Environmental Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Shaping microbial communities and flavor profiles: Effects of native Staphylococcus carnosus and Staphylococcus piscifermentans starter cultures in Chinese dry-fermented sausages - Yufei Zhang; Shasha Zheng; Dewei Huang; Yue Liu; Huilin Cheng; Baocai Xu (Food Research International, 2026)

Different responses of the TGF-β superfamily genes in the warm-water noble scallop Chlamys nobilis to acute and chronic low temperature stress - Shitong Liu; Dewei Cheng; Meizhen Chen; Huiqi Li; Naiqian Zhao; Yaoting Liu; Beiyu Yan; Weili Wang; Hongkuan Zhang; Huaiping Zheng (Aquaculture, 2025)

Antimicrobial effect and mechanism of Sargassum carpophyllum extract against fish spoilage Pseudomonas sp. CL2 - Xin Liu; Qunjian Yin; Fangchao Zhu; Dewei Cheng; Hongzhi Tang; Naibin Yang; Ying Liu (Food Bioscience, 2025)

Physical stability of oil-in-water multi-layered coenzyme Q10 nano-emulsions - Zhili Xu; Fan Zhang; Dewei Cheng; Qianyun Ma; Wenxiu Wang; Jie Wang; Jianfeng Sun (Food Chemistry, 2025)

An Improved Coupled Hydrologic-Hydrodynamic Model for Urban Flood Simulations Under Varied Scenarios - Siwei Cheng; Mingxiang Yang; Chenglin Li; Houlei Xu; Changli Chen; Dewei Shu; Yunzhong Jiang; Yunpeng Gui; Ningpeng Dong (Water Resources Management, 2024)

Characterization of MKK family genes and their responses to temperature stress and Vibrio parahaemolyticus infection in noble scallop Chlamys nobilis - Yetao Zeng; Ruolin Jiang; Jingwen Deng; Dewei Cheng; Weili Wang; Jianming Ye; Cheng He; Chuanxu Zhang; Hongkuan Zhang; Huaiping Zheng (Marine Environmental Research, 2024)

Unveiling hidden interactions: Microorganisms, enzymes, and mangroves at different stages of succession in the Shankou Mangrove Nature Reserve, China - Yongze Xing; Jin Qiu; Jingfu Chen; Dewei Cheng; Qunjian Yin; Xuyang Chen; Li Xu; Pengfei Zheng (Science of The Total Environment, 2024)

The role of corneal endothelium in macular corneal dystrophy development and recurrence - Bi-Ning Zhang; Benxiang Qi; Chunxiao Dong; Bin Zhang; Jun Cheng; Xin Wang; Suxia Li; Xiaoyun Zhuang; Shijiu Chen; Haoyun Duan; Dewei Li; Sujie Zhu; et al. (Science China Life Sciences, 2024)

An epi-allele of SMS causes Sanming dominant genic male sterility in rice - Yachun Yang; Cheng Zhang; Hao Li; Zeyuan Yang; Zuntao Xu; Dewei Tai; Dahu Ni; Pengcheng Wei; Chengxin Yi; Jianbo Yang; Yong Ding (Science China Life Sciences, 2023)

Nitrogen removal characteristics of anammox biofilm and analyses of the dynamic network structure of functional microbes under gradient nitrogen stress - Luowen Cheng; Xuan Wang; Houjie Wu; Dewei Zhang; Jun Zheng (Chemical Engineering Journal, 2023)

Research progress of shell boring mud-blister worm infestation in shellfish aquaculture - Karsoon Tan; Dewei Cheng; Kit Yue Kwan; Ya Peng; Xiahui Cai; Leongseng Lim; Peng Xu; Kianann Tan (Aquaculture, 2023)

Denitrification performance and microbial community analysis of sulfur autotrophic denitrification filter for low-temperature treatment of landfill leachate - Dewei Zhang; Luowen Cheng; Shihua Zhang; Jun Zheng (Journal of Environmental Chemical Engineering, 2023)

Ecological Response to the Diluted Water in Guangxi during the Spring Monsoon Transition in 2021 - Yang Yang; Tinglong Yang; Zhen Zhang; Zuhao Zhu; Li Zhang; Dewei Cheng (Journal of Marine Science and Engineering, 2023)
Based on the field survey data of the Guangxi offshore voyage in May 2021, the distribution characteristics of the wind field during the spring monsoon transition period, the temporal and spatial changes in the diluted water path, and the corresponding ecological responses were analyzed. The results show the following: the core region of diluted water is located along the coast of Guangxi, and the diluted water expands to the east and west at the same time, where the thickness of the diluted water reaches 20 m. Under the combined action of the easterly wind and westward current, the westward expansion trend was stronger than the eastward expansion trend. The surface distribution of suspended solids, chlorophyll a, dissolved oxygen, and active silicon is similar to the dispersion range of the diluted water, and the high-value areas all appear near the estuary, which is basically consistent with the salinity distribution in the core region of the diluted water. Under the mixing caused by the wind and tide in the estuary area, the difference in dissolved oxygen between the surface and bottom layer is small, while in the nearshore area, the stratification of seawater hinders the dissolved oxygen’s downward transmission, resulting in a large difference in dissolved oxygen between the bottom and the surface.

Ceramic ozone catalytic coupling incineration ash and excess sludge recycling with ceftriaxone sodium wastewater treatment: Performance and mechanism - Dewei Zhang; Luowen Cheng; Juntian Zheng; Menglin Wang; Xuan Wang; Shihua Zhang; Jun Zheng (Chemical Engineering Journal, 2023)

Microglia Activation and Polarization After Intracerebral Hemorrhage in Mice: the Role of Protease-Activated Receptor-1 - Shu Wan; Yingying Cheng; Hang Jin; Dewei Guo; Ya Hua; Richard F. Keep; Guohua Xi (Translational Stroke Research, 2016)